ANALISIS SISTEM MANAJEMEN LINGKUNGAN UIN MALANG MENUJU GREEN CAMPUS: PERSPEKTIF EMS ISO 14001 - Isroqunnajah Isroqunnajah; Alfin Mustikawan; Zainur Rofiq (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2022)
A green campus refers to university with an environmental perspective that prioritizes efforts to protect, manage, and preserve the environmental sustainability in higher education (Wimala et al., 2016). This article aims to analyze the feasibility and readiness of UIN Malang management towards a university that is oriented towards environmental well-being in the perspective of ISO 14001. By carrying out a qualitative approach, this study employs top management/leaders, lecturers, employees, students, and relevant documents at UIN Malang as data sources collected through a semi-structured interview and content analysis. The results showed that, to achieve a green campus, the management system of UIN Maulana Malik Ibrahim Malang still unable to meet criteria of a good environmental management system from the perspective of ISO 14001:2015 as there are some basic requirements that have not been fulfilled by the university. To implement ISO 14001-based environmental management system, UIN Malang must create a roadmap that includes a consistent and sustainable management cycle of Plan-Do-Check-Action.